CFEP-mobile: competitive fruit fly optimiser-based energy-aware routing protocol under mobile sink-based WSN. (1st July 2022) - Saoji, Apurva Rushikesh; Rao, Giduturi Srinivasa
Wireless sensor networks (WSNs) are comprised of numerous promising applications from where the sensed data are collected from remote applications. With respect to the promising applications related to data gathering, the desired information from the unreachable or remote locality, WSN poses a major challenge for the energy-efficient routing in data for improving communication. The literature presents several energy-aware routing protocols to maximise the lifespan of the sensor nodes. Consequently, an energy-efficient clustering approach, based on competitive fruit fly optimiser (CFFO) is developed in this paper to enhance the energy and the total lifetime of nodes such that the cluster head is chosen optimally. The hybrid optimisation approach named CFFO, is developed for controlling the convergence rate of the CFFO with the newly designed fitness function by considering the four various objectives like energy, distance, delay, and link lifetime. However, the developed CFFO algorithm is designed by the integration of the competitive swarm optimiser (CSO) and the fruit fly optimisation algorithm (FFOA). This method achieved efficient performance in terms of metrics like PDR, energy, and delay with the maximum PDR of 100%, high energy of 0.367 J, and minimum delay of 0.0925 sec, respectively.